Step-by-step explanation:
[tex]4csc(2x) = 2csc^2(x) tan(x)[/tex]
We start with Left hand side
We know that csc(x) = 1/ sin(x)
So csc(2x) is replaced by 1/sin(2x)
[tex]4 \frac{1}{sin(2x)}[/tex]
Also we use identity
sin(2x) = 2 sin(x) cos(x)
[tex]4 \frac{1}{2sin(x)cos(x)}[/tex]
4 divide by 2 is 2
Now we multiply top and bottom by sin(x) because we need tan(x) in our answer
[tex]2\frac{1*sin(x)}{sin(x)cos(x)*sin(x)}[/tex]
[tex]2\frac{sin(x)}{sin^2(x)cos(x)}[/tex]
[tex]2\frac{1}{sin^2(x)} \frac{sin(x)}{cos(x)}[/tex]
We know that sinx/ cosx = tan(x)
Also 1/ sin(x)= csc(x)
so it becomes 2csc^2(x) tan(x) , Right hand side
Hence verified